2007
DOI: 10.3354/meps329145
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical distribution of cirripede cyprid larvae in an upwelling system off the Portuguese coast

Abstract: . This distribution pattern was considered to result from upwellingfavourable wind conditions, creating fronts along the shelf in which the cyprids become concentrated. Cyprid vertical migration, in association with current vertical shear and onshore movement of fronts during upwelling-relaxation periods, may be the mechanisms returning cyprids to the coast to settle. The regularity of these events in the region falls within the period of cyprid viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…A further point of interest regards the abundances of Chthamalus spp. cyprids recorded during the fixed station study (dos Santos et al, 2007). This study found that C. stellatus larvae were considerably more abundant than those of C. montagui.…”
Section: Larval Pool Assumptionsmentioning
confidence: 59%
“…A further point of interest regards the abundances of Chthamalus spp. cyprids recorded during the fixed station study (dos Santos et al, 2007). This study found that C. stellatus larvae were considerably more abundant than those of C. montagui.…”
Section: Larval Pool Assumptionsmentioning
confidence: 59%
“…These results support the hypothesis that the more thermal stratification there is, the more behavioral control can be exerted by cyprids to accumulate closer to shore, and that stratification is an important determinant of the successful larval transport of cyprid larvae. Nearshore accumulation of cyprid larvae has been previously observed (dos Santos et al 2007, Tapia & Pineda 2007, Shanks & Shearman 2009). We hypothesize that thermal stratification mediates constrained larval distributions in nearshore waters.…”
Section: Discussionmentioning
confidence: 85%
“…While we do not know the vertical migration patterns or preferred depth of larvae of M. coccopoma , larvae were positively phototactic at all instars; likewise, cyprids of other barnacle species are most abundant in surface waters (Pineda ; dos Santos et al. ). Inhabiting deeper waters in the Gulf Stream system would be likely to promote local retention (Hare & Govoni ).…”
Section: Methodsmentioning
confidence: 85%